Anthropometric factors and cutaneous melanoma: Prospective data from the population‐based Janus Cohort. Issue 4 (17th October 2017) - Stenehjem, Jo S; Veierød, Marit B; Nilsen, Lill Tove; Ghiasvand, Reza; Johnsen, Bjørn; Grimsrud, Tom K; Babigumira, Ronnie; Rees, Judith R; Robsahm, Trude E
Abstract : The aim of the present study was to prospectively examine risk of cutaneous melanoma (CM) according to measured anthropometric factors, adjusted for exposure to ultraviolet radiation (UVR), in a large population‐based cohort in Norway. The Janus Cohort, including 292, 851 Norwegians recruited 1972–2003, was linked to the Cancer Registry of Norway and followed for CM through 2014. Cox regression was used to estimate hazard ratios (HRs) of CM with 95% confidence intervals (CIs). Restricted cubic splines were incorporated into the Cox models to assess possible non‐linear relationships. All analyses were adjusted for attained age, indicators of UVR exposure, education, and smoking status. During a mean follow‐up of 27 years, 3, 000 incident CM cases were identified. In men, CM risk was positively associated with body mass index, body surface area (BSA), height and weight (all p trends  < 0.001), and the exposure‐response curves indicated an exponential increase in risk for all anthropometric factors. Weight loss of more than 2 kg in men was associated with a 53% lower risk (HR 0.47, 95% CI: 0.39, 0.57). In women, CM risk increased with increasing BSA ( p trend  = 0.002) and height ( p trend  < 0.001). The shape of the height‐CM risk curve indicated an exponential increase. Our study suggests that large body size, in general, is a CM risk factor in men, and is the first to report that weight loss may reduce the risk of CM among men. Abstract : What's new? Anthropometric factors, such as height and weight, affect melanoma risk, according to new results. These authors looked at data from a large Norwegian cohort, including 3000 cases of cutaneous melanoma. They found that body mass index, body surface area, weight, and height all influence CM risk in males, with an exponential increase for all factors. In women, only height and body surface area correlated with cancer risk – possibly because women with higher weight and BMI sunbathe less. They further showed that men who reduced their weight by 2 kg or more also lowered their melanoma risk.